2019
DOI: 10.1186/s12938-019-0736-0
|View full text |Cite
|
Sign up to set email alerts
|

A current-mode system to self-measure temperature on implantable optoelectronics

Abstract: BackgroundOne of the major concerns in implantable optoelectronics is the heat generated by emitters such as light emitting diodes (LEDs). Such devices typically produce more heat than light, whereas medical regulations state that the surface temperature change of medical implants must stay below + 2 °C. The LED’s reverse current can be employed as a temperature-sensitive parameter to measure the temperature change at the implant’s surface, and thus, monitor temperature rises. The main challenge in this approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The temperature-sensing functionality was tested by interfacing various mini-LEDs in saline tissue models prior to in vivo surgery, and the developed circuits were experimentally characterized. With an operating frequency of up to 130 kHz, the outcomes of the experiment demonstrate the versatility the reliability of the CCII-based technique and the efficiency of CMOS electronics achieving a 0.2°C resolution for surface temperatures up to +45°C [12].…”
Section: Introductionmentioning
confidence: 86%
“…The temperature-sensing functionality was tested by interfacing various mini-LEDs in saline tissue models prior to in vivo surgery, and the developed circuits were experimentally characterized. With an operating frequency of up to 130 kHz, the outcomes of the experiment demonstrate the versatility the reliability of the CCII-based technique and the efficiency of CMOS electronics achieving a 0.2°C resolution for surface temperatures up to +45°C [12].…”
Section: Introductionmentioning
confidence: 86%
“…F, Relationship among junction current, surface temperature, and junction temperature variation when the LED is driven using a 2.5 mA pulse in water and the base temperature is 37 C. G, Output current and voltage; the surface temperature of the LED is driven using a 7.5 mA pulse in water. H, Extracted surface temperature variation; LED with 2 mA and 4 mA currents for 1 min 104 [Colour figure can be viewed at wileyonlinelibrary.com] human body (43 C) when handling implantable devices. They developed a 2D axisymmetric transient equivalent model of an implantable device's radio energy transmission to simulate the temperature variation of the metal shell at the receiving end.…”
Section: Operating Temperaturementioning
confidence: 99%
“…The temperature change limit for a device must be below +2 C to reduce the tendency of various internal and component damages. Dehkhoda et al 104 developed an area-efficient light-emitting diode (LED)-based temperature sensor by using LED to ensure stable bias and current measurement. They adopted a second-generation current conveyor configuration and realized a resolution of 0.2 C for a frequency of 130 kHz at a surface temperature of 45 C. The study was designed for monitoring tissue surface temperature in optogenetics, as shown in Figure 5, and can provide low power and a robust system to a device.…”
Section: Operating Temperaturementioning
confidence: 99%
See 1 more Smart Citation